2007
DOI: 10.1002/mde.1375
|View full text |Cite
|
Sign up to set email alerts
|

Follow the leader: price change timing in Internet‐based selling

Abstract: Internet technologies should lessen information asymmetry, prompting competitive price reactions, but this does not seem to be happening in Internet-based selling. We study empirical regularities of price change timing for music CD vendors and booksellers to assess several theoretical explanations. Our sample includes 123, 680 daily prices for 169 products and 53 firms. Bertrand competition is insufficient to explain our observation that sellers do not shift prices this way. Tacitly collusive responses to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…We also found that searching (both self-reported and observed in our experiment) leads to higher levels of institutional-based trust and experience. In addition, although other research contends that established institutions, like eBay and PayPal, should command higher bid levels (Brynjolfsson & Smith, 2000;Kauffman & Wood, 2007), our findings are consistent with the results of Stewart (2003) and Kim (2008). They found that the institutional-based trust which certain individuals develop for one online institution can be transferrable to similar institutions.…”
Section: Figure 3 -Structural Equation Modelsupporting
confidence: 90%
“…We also found that searching (both self-reported and observed in our experiment) leads to higher levels of institutional-based trust and experience. In addition, although other research contends that established institutions, like eBay and PayPal, should command higher bid levels (Brynjolfsson & Smith, 2000;Kauffman & Wood, 2007), our findings are consistent with the results of Stewart (2003) and Kim (2008). They found that the institutional-based trust which certain individuals develop for one online institution can be transferrable to similar institutions.…”
Section: Figure 3 -Structural Equation Modelsupporting
confidence: 90%
“…In theory, as Reibstein [2002] notes consumers must be in a position to access and more importantly utilise all the relevant information, with respect to a particular purchase decision, if perfect markets are to evolve. However, in practice consumers don't have the time, confidence, desire, and most importantly knowledge, to always make optimal decisions [Kauffman and Wood 2007], as too often, consumers are now simply 'spoilt for choice' [Earl & Mandeville, 2009]. Moreover, it can be argued that the early predictors of perfect competition failed to take into account the importance of 'first mover advantage', and the very significant 'fixed costs' associated with setting up a successful on-line business [Earl & Mandeville, 2009].…”
Section: The Transformation Of the Market-placementioning
confidence: 99%
“…Thanks to the Internet sellers can adopt new strategies such as rapid reactions to promotions, price tracking, price signalling etc. (Kauffman and Wood, 2007). As in the analysis of CPI data, we cannot exclude that our results are affected by the behaviour of new firms entering and/or seeking to foster their market position.…”
Section: Introductionmentioning
confidence: 99%